LA BARRERA LINGÜÍSTICA EN REMISIÓN Y EL ACCESO A LA JUSTICIA EN LA CORTE SUPERIOR DE JUSTICIA DE PUNO - Pineda Gonzales, José Alfredo (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
Legal interculturality constitutes the interaction of human groups with different cultures in terms of norms, procedures, principles or behaviors considered legal by the same group. Access to ordinary justice for indigenous peoples constitutes a real challenge since they have to counteract barriers both in territorial coverage due to the excessive judicialization of conflicts, as well as excessive formalities, and, as we will analyze in this investigation, the dominant use of the Spanish language, which would limit the right of access to justice of the Aymara or Quechua-speaking procedural parties. It is precisely about these barriers that the present investigation is concerned, which aims, as an objective, to verify the access of Quechua and Aymara language litigants to the judicial service in the Superior Court of Justice of Puno. Regarding the applied methodology, this is descriptive- hermeneutic, since it is a work of description of reality and of an interpretive nature, since the purpose is to understand, interpret, deepen the meanings from the point of view of the actors in the problem and establish relationships between the meanings and the context. The technique of analysis will be the Qualitative Analysis. The results obtained in the investigation in relation to the linguistic barriers in the justice service that is offered in the Superior Court of Justice of Puno have had a development of progressive advance; This is how the manifest reality has been verified in 2011, through an investigation on access to justice for Quechua and Aymara-speaking litigants, finding clear difficulties for the corresponding access to the justice system. In an evolutionary view and with the passing of time, it has been possible to verify that this barrier has been gradually and effectively eliminated through training actions, assignment of suitable personnel to attend to the litigating public in the Aymara and Quechua language, drafting of resolutions finals in Quechua and Aymara, and the implementation of a system of translators and interpreters, thereby facilitating full access to the judicial system.